Quantitative Rice Postharvest Losses in the Albertine and Olweny Rice Hubs, Uganda - John, Yawe; Alphonse, Candia; Lawrence, Obeti Grism (International Journal of Scientific Research and Management (IJSRM), 2019)
Since the introduction of rice in Uganda in 1904, insufficient information has been generated on quantitative rice postharvest losses. Such inadequate information has partly constrained decision making in developing the rice industry in Uganda. The objective of this study was, therefore, to generate quantitative postharvest losses in the remaining two major rice growing hubs of Albertine and Olweny. The AfricaRice postharvest loss assessment methodology was used during the two growing seasons of 2014 /15 and 2015/16. Data was collected at harvesting, threshing, drying and milling postharvest stages on 10 rice farms and nine rice mills in each hub. The swamp rice “K98” and “NERICA-4” both in Oryza Sativa group were used during the study in the Olweny and Albertine hubs respectively. The results indicated that total physical grain losses at aforementioned stages in Albertine and Olweny hubs were 16.8 and 14.1%, respectively. This slight loss variation could be attributed to the different varieties and postharvest practices in these hubs. Losses at harvesting exhibited highest value 6.9 and 5.7% compared to threshing 4.7 and 4.8%; drying 1.8 and 1.4%; and milling 4.8 and 3.5% for Albertine and Olweny hubs respectively. There was no significant difference (p>0.05) discerned in the losses between the hubs. Regardless of the rice hub, significant differences in loss levels (p